Understanding pilots’ acceptance to operate in an integrated airspace with crewed and uncrewed aircraft - Vinod D.; Brett Robert Charles Molesworth (Drone Systems and Applications)
The safe integration of new and emerging technologies such as remotely piloted aircraft (RPA) into existing airspace will require pilots’ acceptance of such technology. Therefore, the main aim of the present research is to understand pilots’ willingness to operate with crewed and uncrewed aircraft in an integrated airspace. The research also aims to examine whether factors such as vertical separation, automation levels, and technology acceptance affect pilots’ level of airspace integration acceptance. Eighty-five pilots completed a battery of surveys, comprising a demographics questionnaire, a technology acceptance questionnaire, as well as a newly created Aircraft Separation Questionnaire. The results revealed a clear automation acceptance threshold in acceptance between automation levels 3 and 4, the point at which decision-making transitioned from the human to the automation. The analysis found no significant relationship between vertical separation and technology acceptance. These results illustrate that pilots are more receptive towards integrated airspace operations when controlling decisions are undertaken by a human.